To Evaluate and Compare the Microleakage of Chitosan Nano Hydrogel-Incorporated MTA and Glass Ionomer Cements When used as a Retrograde Filling Material - Vinaykumar G. Suryavanshi; Ravi K. Tale; Vivekanand D. Kolvekar; Rashmi Chordiya; P S Amal; B Abijeet (Journal of Pharmacy and Bioallied Sciences)
Background: An inadequate apical seal stands out as a primary cause of disappointment in surgical endodontic procedures. Therefore, the choice of root-end filling material should aim to prevent the leakage of potential contaminants into the periapical tissue. Aim: To evaluate and compare microleakage of chitosan nano hydrogel-incorporated mineral trioxide aggregate (MTA) and glass ionomer cement (GIC) when used as a retrograde filling material. Materials and Methods: Sixty single-rooted premolars were decoronated at cemento enamel junction (CEJ), and root canals were prepared and obturated, with the coronal part sealed with a composite. The dye absorption was measured by an automatic spectrophotometer. Results: The results showed that the MTA + chitosan group had less microleakage values compared to the MTA group but was not statistically significant and GIC + chitosan had less microleakage values compared to the GIC group and was statistically significant. Conclusion: Chitosan-incorporated MTA and chitosan-incorporated GIC can be considered as retrograde filling material; however, further in vitro and in vivo research and long-term clinical studies are required.